SUPRASEGMENTAL SOUNDS PRODUCED BY THE STUDENTS OF ENGLISH EDUCATION DEPARTMENT AT UIN ALAUDDIN MAKASSAR - Azisah, Nadya Nur; Kaharuddin, Kaharuddin; Said, Abdul Muis (English Language Teaching for EFL Learners Journal, 2021)
This study aims to see the extent the ability of students to pronounce English words who have studied English for many years and studied phonetics, then compare it with the pronunciation of native English speakers. The benefit of this research is that it can increase students' awareness in improving their speaking skills by trying to find new strategies to support their skill improvement. Phonetic and phonology theory is used as concept of this study. The research uses descriptive qualitative method with data collection techniques through recording to retrieve the audio of the samples and native English speaker, then insert it into the gold wave editor to then see the high and low amplitude of the sound. This study focuses on suprasegmental sound especially stress and intonation.The findings of this study showed two things i.e. first, for the stress level, the English students pronounced the words slower and clearer and they also pauses within two words more frequently than the English native speaker and it indicates that the word is stressed with primary or secondary stress. In contrast, the native English speaker pronounced the English words faster than between a word and the coming word and more frequently than the English student. And it indicates that the word is stressed with unstressed (weak stress). Second, the difference of the intonation contour The English native speaker pronounces some words and juncture within two words more frequently, so the intonation contours of her utterances are more falling than rising. On the other hand, English students pronounce the words slower, clearer and gave pause within two words, consequently the amplitude of the words were higher and at the result the rising intonation contour more than falling intonation contour.